THE DISTRIBUTION OF HEPATITIS B VIRUS GENOTYPES AND SUBGENOTYPES IN ACUTE AND CHRONIC INFECTIONS. AND THE IDENTIFICATION OF AMINO ACIDS SUBSTITUTIONS IN ADDITION TO ALLELE FREQUENCY - Mohammed Mhmood; Songül Şahin; Laith Najeeb; Pinar Arslan; Başak Karasu (Journal of Medical Genetics and Clinical Biology, 2024)
Infection with the hepatitis B virus (HBV) is a worldwide health concern, Genotyping HBV is important because it can help to guide treatment decisions, and the risk of developing severe liver disease can be predicted with the use of HBV genotyping, like hepatocellular carcinoma and cirrhosis. Our study aimed to determine HBV genotype and Allele frequencies in acute, and chronic HBV patients living in Al-Anbar governorate/Iraq. samples were analyzed by nested PCR for hepatitis B virus DNA. Round 1 PCR products revealed that all samples of hepatitis B patients showed a 1003 bp band, which confirmed that the current sample was infected with the virus, Second-run PCR demonstrated a pattern of nested PCR products with a 600 bp band. The amplicons from nested PCR were sequenced by the Sanger sequencing method and each viral genotype was investigated and ascertained by alignment with the reference sequence (GenBank acc. NC 003977.2) and blasted using the NCBI blastin database. The results showed the only type D genotype was found in all 80 HBV patients, with seven nucleic acid variants observed in the investigated samples in different positions, namely 348 T>C, 495 C>T, 501 A>C, 520 C>A, 522 G>A, 530 T>C, and 535 A>C. Additionally, ten variants of amino acids were found in different positions to exhibit effects on the S protein within the size of the amplified loci.